Advancing Fab-Compatible Color-Selective Organic Photodiodes: Tailored Molecular Design and Nanointerlayers - Pyo, Won Jun; Kim, Gyuri; Kim, Sinwon; Oh, Haechan; Keum, Dongki; Kim, Byoungin; Kim, Dowan; So, Chan; Lee, Sangjun; Jee, Dong Woo; Jung, In Hwan; Chung, Dae Sung (ACS Nano, 2024)
High-performance organic photodiodes (OPDs) and OPD-based image sensors are primarily realized using solution processes based on various additives and coating methods. However, vacuum-processed OPDs, which are more compatible with large-scale production, have received little attention, thereby hindering their integration into advanced systems. This study introduces innovations in the material and device structures to prepare superior vacuum-processed OPDs for commercial applications. A series of vacuum-processable, low-cost p-type semiconductors is developed by introducing an electron-rich cyclopentadithiophene core containing various electron-accepting moieties to fine-tune the energy levels without any significant structural or molecular weight changes. An additional nanointerlayer strategy is used to control the crystalline orientation of the upper-deposited photoactive layer, compensating for device performance reduction in inverted, top-illuminated OPDs. These approaches yielded an external quantum efficiency of 70% and a specific detectivity of 2.0 × 1012 Jones in the inverted structures, which are vital for commercial applications. These OPDs enabled visible-light communications with extremely low bit error rates and successful X-ray image capture.
Keywords: Commercial applications; Molecular design; Nanointerlayer; New donor; Organic image sensor; Organic photodiodes; Organics; Performance; Visual-light communication; X ray sensors; nanointerlayer; new donors; organic image sensor; visual-light communication; X-ray sensors